Zoom Rendering: Improving 3-D Rendering Performance with 2-D Operations - Mazuryk, Tomasz; Schmalstieg, Dieter; Gervautz, Michael (International Journal of Virtual Reality, 1996)
We propose a new method to accelerate rendering during the interactive visualization of complex scenes. The method is applicable if the cost of per-pixel processing is high compared to simple frame buffer transfer operations, as supported by low-end graphics systems with high-performance CPUs or 2-D graphics accelerators. In this case rendering an appropriately down-scaled image and then enlarging it allows a trade-off of rendering speed and image quality. Using this method, more uniform frame rates can be achieved and the dynamic viewing error can be reduced.